A Methodological Advance of Tobacco Rattle Virus-Induced Gene Silencing for Functional Genomics in Plants - Shi, Gongyao; Hao, Mengyuan; Tian, Baoming; Cao, Gangqiang; Wei, Fang; Xie, Zhengqing (Frontiers in Plant Science, 2021)
As a promising high-throughput reverse genetic tool in plants, virus-induced gene silencing (VIGS) has already begun to fulfill some of this promise in diverse aspects. However, review of the technological advancements about widely used VIGS system, tobacco rattle virus (TRV)-mediated gene silencing, needs timely updates. Hence, this article mainly reviews viral vector construction, inoculation method advances, important influential factors, and summarizes the recent applications in diverse plant species, thus providing a better understanding and advice for functional gene analysis related to crop improvements.